Predictors of Counseling Self-Efficacy: Examining Counselor Trainee’s Perception of Supervisory Interaction Style - Poonam V Doshi; Alfred W Ward; Rostyslaw W Robak (Teaching and Supervision in Counseling, 2022)
Abstract: The present research examined the relationship between perceived supervisory autonomy support and counseling self-efficacy (CSE) of counselor trainees. We explored whether this relationship was mediated by autonomous work motivation using the framework of self-determination theory (SDT; Ryan & Deci, 2017) . Participants were master’s level mental health counseling interns (n = 182) enrolled in field internships. Mediational analyses showed that autonomous work motivation partially mediated the relationship between perceived autonomy support from supervisor and counselor trainees’ CSE. Results underscore the importance of adopting autonomy-supportive styles of clinical supervision for enhancing counselor trainees’ counseling self-efficacy. What is the public significance of this article?: This study suggests that when clinical supervisors provide an environment that supports counselor trainees’ autonomy, trainees experience increased autonomous motivation, which further enhances their counseling self-efficacy.
Keywords: clinical supervision; autonomy support; counseling self-efficacy